Analyzing the Correlation Between University Rankings and the Economic Performance of Countries - Aslı Günay (Üniversite Araştırmaları Dergisi)
The main objective of this study is to examine the correlation between university rankings and the economic performance of countries, if university rankings are used as a proxy for the quality of higher education. The findings indicate that there is a correlation between the GDP (or the size of the country’s economy) and the number of universities in the top 500, but there is no correlation between the employment rate and the number of universities in the top 500 by the year of 2019. Hence, the results imply that GDP value rather than the employment rate of countries has an impact on university rankings (or the quality of higher education). Since it is thought that countries with higher or better levels of education, both in terms of quantity and quality, will also have stronger economic growth, the findings of this study could help policymakers make decisions about higher education and the economy.